The Influence of Angklung Extracurricular in Increasing Love for Sundanese Culture - Clara Debbyta Wulandari; Rina Maryanti (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of this research is to increase love for Indonesian culture, especially West Java culture, which is held in angklung learning activities for school students. 178 Public Elementary School of Gegerkalong. Therefore, teachers must provide learning methods that make it easier for children to learn the traditional musical instrument angklung. Before being given angklung learning, students did not understand the types of angklung originating from West Java and did not understand how to play angklung. Then we did the research. The steps we took to get the results, firstly by conducting qualitative descriptive research, namely describing, describing, and describing the problems studied. We ask students to fill out PreTest and PostTest in Google Form link first. Second, we teach the song Tokecang which is a folk song of West Java with the learning method while playing in the classroom. The average value obtained is PreTest 66.5 and there is an increase after doing PostTest, with an average value of 93.5. From these results indicate that the research was successfully carried out. The impact that occurs after being given learning about angklung is that students are enthusiastic to practice and want to preserve the angklung musical instrument by introducing the angklung game in events held at school.